Castellu (Haute-Corse) Un établissement rural de l'Antiquité tardive : fouilles récentes (1981-1985) - Pergola, Philippe; Vismara, Cinzia (Documents d'archéologie française, 1989)
The publication of excavations at Castellu throws an entirely new light upon late-Roman and early-medieval Corsica. The study includes an examination of the finds, most of which are of 6th century date, and an analysis of the faunal remains. The latter shows not only that domesticated species differed from those of the Iron-Age but also that eating habits had changed. The resulting picture is one of significant and long-lasting Romanisation of innerCorsica, and of ongoing trade relations with the rest of the Mediterranean region, even after the Vandal invasion. The publication marks a major step towards a new understanding of this period of Corsican history.